Analysis of the Processes of Short-Currents Limiting by Transformer with High-Temperature Superconducting Windings - Manusov V.Z.; Pavlyuchenko D.A.; Ahyoev J.S. (Problems of the Regional Energetics)
An important advantage of transformers with high-temperature superconducting winding is their ability to limit the short-circuit currents. The article discusses a physico-mathematical model that analyses transient processes at short-circuit currents in electrical networks containing transformers with a high-temperature superconducting winding. One of the main ideas and objectives of this work is to investigate the process of short-circuit currents limiting by means of a transformer with a high-temperature superconductor winding, which makes it possible to combine two series-connected elements in one device: transformer and a reactor. The effectiveness of this method is due to the fact that when the short-circuit currents exceed the critical value of the temperature of the superconductor winding, it goes to the normal state with high winding resistance for short-circuit currents. It is important to know when a superconductor should go over to a normal state with the loss of superconductivity. For this purpose, a program was developed to determine the amount of heat generated by a short-circuit current flowing before it is disconnected. For a transformer with high-temperature superconducting winding with a capacity of 40 MVA, a short circuit must be eliminated after 0.1 seconds, without switching off the transformer. To limit the short-circuit current; it is intended to use a hybrid winding. The performed assessment showed that the return of the winding to the superconducting state, first, depends on the ratio of the short-circuit currents to the operating current. This is the criterion for the return/non-return to the superconducting state.